Reality of Sharia Banking System (Study of Islamic Economic Development In Indonesia) - Anton Priyo Nugroho; Hatidah Hatidah; Muhammad Iqbal; RA Rodia Fitri Indriani; Abdul Rahman Ramadhan (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2023)
A discussion of Islamic economics has previously been introduced in the fields of science and society. In the midst of numerous traditional social and economic systems based on secular materialism, Islamic economics is a reality that continues to demonstrate its excellence. Islamic economics is likewise a scientific reality that consistently distinguishes itself from social science constellations founded on atheism and even secularism. Islamic economics is a new force within these two streams that is developing into a mature, independent system and discourse in scientific thinking. Its existence is a culmination of long-lasting intellectual attempts in the history of the Muslims as well as a reaction to the inequity of the contemporary socio-economic system.